The Spectroscopic Behaviour of Rhodamine 6G in Liquid and Solid Solutions (Baghdad Science Journal, 2008)
Absorption, fluorescence, quantum yield and lifetime of rhodamine 6G in chloroform, methanol and dimethyl sulfoxide were measured. From a comparison of these quantities, with those for solid solutions (solid solutions are obtained by mixing constant volume proportions of dye at a concentration of 1*10-4M/l with different volume proportions from the concentrated solution of polymer in chloroform and dimethyl sulfoxide).The results showed that the addition of polymer to liquid concentrated solutions (1*10-4M/l )of rhodamine 6G dye from expecting [which leading to development active medium for laser dye at high concentration] increase the spectra shift toward high energies, and the luminescence quantum yield but decreasing radiative lifetime.